Mycobacterium tuberculosis EspR modulates Th1-Th2 shift by transcriptionally regulating IL-4, steering increased mycobacterial persistence and HIV propagation during co-infection - Yandrapally, Sriram; Agarwal, Anushka; Chatterjee, Archismita; Sarkar, Satarupa; Mohareer, Krishnaveni; Banerjee, Sharmistha (Frontiers in Immunology, 2023)
Mycobacterium tuberculosis (Mtb) and HIV are known to mutually support each other during co-infection by multiple mechanisms. This synergistic influence could be either by direct interactions or indirectly through secreted host or pathogen factors that work in trans. Mtb secretes several virulence factors to modulate the host cellular environment for its persistence and escaping cell-intrinsic immune responses. We hypothesized that secreted Mtb transcription factors that target the host nucleus can directly interact with host DNA element (s) or HIV LTR during co-infection, thereby modulating immune gene expression, or driving HIV transcription, helping the synergistic existence of Mtb and HIV. Here, we show that the Mtb-secreted protein, EspR, a transcription regulator, increased mycobacterial persistence and HIV propagation during co-infection. Mechanistically, EspR localizes to the nucleus of the host cells during infection, binds to its putative cognate motif on the promoter region of the host IL-4 gene, activating IL-4 gene expression, causing high IL-4 titers that induce a Th2-type microenvironment, shifting the macrophage polarization to an M2 state as evident from CD206 dominant population over CD64. This compromised the clearance of the intracellular mycobacteria and enhanced HIV propagation. It was interesting to note that EspR did not bind to HIV LTR, although its transient expression increased viral propagation. This is the first report of an Mtb transcription factor directly regulating a host cytokine gene. This augments our understanding of the evolution of Mtb immune evasion strategies and unveils how Mtb aggravates comorbidities, such as HIV co-infection, by modulating the immune microenvironment.